THE LEVEL OF SOCIAL COMMITMENT AMONG UNIVERSITY STUDENTS - Mohammad Omar AL-Momani; Elham Mahmoud Rababa (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
The study aimed to identify the level of social commitment among university students and its relationship to the gender variable, where the descriptive approach was used in addition to the use of a questionnaire consisting of (24) items as a tool for the study, and the study sample consisted of (1247) male and female students from different Jordanian universities, in The second semester of the academic year (2020/2021), and the study concluded that university students in general have a degree of social commitment greater than the hypothetical average of the scale, and this indicates that the result is positive for them , in addition to the existence of significant differences in the degree of social commitment among university students. According to the gender variable (males, females),  and in favor of females.